PENGARUH BIAYA PRODUKSI DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Maulidya Masputri Ambarini (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
The research was conducted to determine the effect of production costs and sales volume on net income on food and beverage sub-sector manufacturing companies listed on the IDX for the 2012-2016 period. In this study researchers used the population, namely food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange with a sample of the company`s financial statements with a total of 15 companies in the 2012-2016 period and only 10 companies that had criteria according to the variables chosen by the determining the sample is type of research is quantitative research, and the technique of determinating the sample is sampling purposives which numbered 10 company financial statments and the data analysis used was SPSS (Statistical Package for Social Science). The result showed that the Production Cost variables had a significant positive effect on Net Profit with a significance value 0f 0,000 and the Sales Volume variable also had a significant positive effect on Net Income with asignificance value of 0,009.